Microbiology - Prescott, Lansing M. (McGraw-Hill, 2005)
Prescott, Harley and Klein's 6th edition provides a balanced, comprehensive introduction to all major areas of microbiology. Because of this balance, Microbiology, 6/e is appropriate for students preparing for careers in medicine, dentistry, nursing, and allied health, as well as research, teaching, and industry. Biology and chemistry are prerequisites. --This text refers to an out of print or unavailable edition of this title.